(3QSGdI aj HjGf eSFdJGf gfOSjJGfs - (3nhrjnLf Hf QSJe Gdochgj (B( (3Gdbhgj (B) (3, CHh Sgd,J (B390 (3g` s
(3ChdgG (B:s
(3OGFQI C H eYdheI heQcRgG W hbWQgG C W H hbO JYdeJ Ydjg fbWI cja GJabJ hgj fbWI O hGNQL bWQ C H ai cdJi GdLgJjf Edi fbWJi O g` s
(3BNQgG (B:s
(3afSHI eLehY CH O Q Edi eLehY C O O L` cfSHI U Y Edi Y b hPdc eG CQOfG Cf fHjf JeJ GdeSFdI GdKGfjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGef YTQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B175s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs